Nutritional assessment of bread wheat genotypes in relation to processing quality and yield related attributes - Kumar, Parminder; Mavi, Gurvinder Singh; Kaur, Harinderjeet; Sohu, Virinder Singh (Journal of Cereal Research, 2024)
Wheat is an important constituent of cereal-based diet that contributes to human health. However, existing wheat varieties are low in protein and micronutrients that lead to malnutrition. Biofortification is an emerging, successful sustainable approach to alleviate the problem. However, for production of different type of food products these varieties must fulfill the minimum quality criteria. In this study, 1520 genotypes were analyzed for their iron (Fe), zinc (Zn), and phytic acid content. Additionally, eleven selected genotypes were evaluated for various physiological and yield parameters. The study identified significant variability in Fe and Zn concentrations in mature grain, with concentrations ranging from 21.8 to 71.4 ppm for Fe and 20.4 to 84.3 ppm for Zn. A positive correlation between Fe and Zn suggests the potential for concurrent nutrient enhancement through breeding. Phytic acid levels varied from 0.11% to 0.48%, impacting nutrient bioavailability. Hierarchical clustering of genotypes revealed eight clusters, with Cluster III standing out for high Zn (>60 ppm) and low phytic acid (<0.20%). The eleven selected genotypes demonstrated high protein content, excellent milling quality, and competitive yields. Notably, they also showed favorable canopy temperatures, indicating heat tolerance. Overall, these genotypes offer promising prospects for improving both nutritional value and agronomic performance in future breeding programs.